What explains the decline in wage mobility in the German low-wage sector? - Bodo Aretz; Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
In this paper, we study how wage mobility in the low-wage sector has changed in western Germany between 1984 and 2004. Using German individual register data, we document a clear upward trend in the persistence of low-wage employment for both men and women. Next to compositional shifts of the low-wage sector relative to the high-wage sector, this trend may be explained by an increase in genuinestate dependence, which occurs if low-wage employment today causes lowwage employment in the future for reasons of, e.g., stigmatization or human capital depreciation. To isolate the latter, we model low-pay transitions by estimating a series of multivariate probit models. We address the initial conditions problem and the endogeneity of earnings attrition in our estimation approach by accounting for the selection into low-wage employment and earnings retention. Our findings for men and women point to an upward trend of genuine state dependence among low paid workers especially since the beginning of the 1990s. Using decomposition techniques, we show that between 35 and 54 per cent of the increase in genuine state dependence during the 1990s is accounted for by compositional effects.
Keywords: C23; J31; L13; 330; Wage Mobility; Trivariate Probit; Administrative Data